KONDISI LINGKUNGAN DAN KARAKTERISTIK SOSIAL BUDAYA UNTUK PENGELOLAAN DAERAH ALIRAN SUNGAI (Studi Kasus pada Suku Dani di Jayawijaya, Papua) (Environmental conditions and socio-cultural characteristics for watershed management (Case study at Dani tribe, Jayawijaya, Papua)) - Baharinawati W. Hastanti (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2017)
Upper of Mamberamo watershed located at Jayawijaya regency, a plain (valley) in Jayawijaya mountains, that known as the Baliem valley.  In this valley lies Tariratu river (Idenburg river) which is a tributary of Mamberamo river. Dani tribe, the oldest tribe inhabits this fertile region. In addition to known as belligerent, Dani tribe known as swidden farmers with certain traditional wisdom to maintain the soil fertility. Environmental condition and socio-cultural characteristics community in managing the upper watershed influence the watershed management, especially in the downstream. This study aims to determine the environmental and socio-cultural characteristics of the Dani tribe in managing the natural resources in the upper watershed to support Mamberamo watershed management. This study was conducted at Wamena, Jayawijaya regency, Papua province. This research is qualitative descriptive research. Data collections was conducted by interviews and literature studies. The data were analysed qualitatively and described the environmental conditions and socio-cultural characteristics of people in the upper watershed of Mamberamo or Baliem watershed is the major element in the management of the Mamberamo watershed. The upper watershed has a conservation function to reduce land degradation. The Dani tribe in the upper Mamberamo has local wisdoms that support the vegetation, soil and water conservation’s function.